"Granny" au pairs in online French news media: a crueller shade of optimism?. Issue 6 (1st November 2016) - Ringrose, Priscilla
Abstract: This article examines the French media representation of low-cost live-in "granny" au pairing services available to French families in France and abroad. It argues that the French news broadcast media repackage "granny" au pairing as positive ageing while underplaying its status as work. The media not only gloss over the low (or no) payment these older single women receive, but also sidestep the precarious economic conditions which motivate them to undertake this work. Instead of portraying au pairs as underpaid workers, it promotes au pairing as "good-life fantasies" and au pairs as active agers. "Granny" au pairs are framed as glamorous, adventurous tourists, or as devoted super grannies. Following Lauren Berlant's notion of "cruel optimism, " I argue that the media promote these fantasies despite the lack of evidence of reciprocity in the au pairs' surrogate family relations and working arrangements. There is a sense of cruel optimism in the way these fantasies deny the reality of au pairing as work, assume that older citizens should find private solutions for inadequate pensions, and reinforce the idea that constant activity is what is required of older single women.